Sistem ekonomi Islam : zakat dan wakaf - Ali, Mohammad Daud (Jakarta : Penerbit Universitas Indonesia, 1988)
Islamic economic system and its application in Indonesia.
Includes bibliographical references and index.
Keywords: Islam -- Economic aspects -- Indonesia; Waqf -- Indonesia; Zakat